TEACHERS’ PERSPECTIVE ON THE CHALLENGES OF TEACHING ENGLISH FOR SPECIFIC PURPOSES IN INDONESIA - Wahyunengsih Wahyunengsih (Journal of English for Academic and Specific Purposes, 2018)
Many studies related to EFL investigate that a mismatch betweenteaching and learning styles cause learning failure, frustration, anddemotivation. The implementation of ESP in Indonesia mostly adoptsContent-Based Instruction which requires a lot of effort from the teacher.The teachers’ perspectives are important to reveal the actual challenges inthe classroom to determine the best solution. A questionnaire wasdistributed to around thirty lecturers of ESP to be analyzed statistically byusing the Likert scale to show their views on the obstacles and challengesof teaching ESP. There are four domains that are analyzed which are,opinions, attitudes, preferences, and perceptions of the subjects. Theresearcher counted and found out the average score, middle point in thescore distribution, point where the most score was obtained, finding theaverage deviation of each score from the mean, and percentage of theproportion of the group population. From all of those calculation results,the researcher derives conclusion by comparing to the result of theinterview as well. It comes to the conclusion that from four fields thathad been studied, attitudes and preferences take the highest rank of theteachers’ challenge.